REPRESENTASI EFEK BURUK MEDIA SOSIAL PADA FILM “BUDI PEKERTI” KARYA WREGAS BHANUTEJA - Alifatun Mahbubah; Muhammad As’ad (JURNAL ILMIAH NUSANTARA, 2025)
This study examines two issues: (1) How are the negative effects of social media represented in Wregas Bhanuteja's film Budi Pekerti? and (2) How are the meanings of these signs interpreted using Charles Sanders Peirce's semiotic model? This study aims to reveal how the negative effects caused by social media are represented through the film Budi Pekerti. This study uses a non-scene qualitative approach with data collection techniques conducted through observation of scenes in the film Budi Pekerti that represent how social media can have negative effects. Data was also obtained from documentation and literature studies. The object of this research is the film Budi Pekerti by Wregas Bhanuteja, and the subject of the research is the negative effects of social media represented in the film Budi Pekerti using Charles Sanders Peirce's semiotic approach. The results of this study indicate that cyberbullying, negative framing, cancel culture, social pressure, and even job loss caused by misunderstandings due to news spread on social media. This study concludes that Budi Pekerti is a film that reflects everyday life in society and also serves as a critique of social media users who are unwise or irresponsible.